2019
DOI: 10.1016/j.jsams.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response between frequency of breaks in sedentary time and glucose control in type 2 diabetes: A proof of concept study

Abstract: Objectives: This study aimed to investigate dose-response between frequency of breaks in sedentary time and glucose control.Design: Randomised three-treatment, two-period balanced incomplete block trial.Methods: Twelve adults with type 2 diabetes (age, 60±11 years; body mass index, 30.2±4.7 kg/m 2 ) participated in two of the following treatment conditions: sitting for 7 hours interrupted by 3 min lightintensity walking breaks every (1) 60 min (Condition 1), (2) 30 min (Condition 2), and (3) 15 min (Condition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Experimental studies have generally supported this evidence and shown that avoiding prolonged sedentary bouts with light‐intensity activities (eg, walking) could be beneficial for cardiometabolic health in adults 3 . For instance, consistent with our results, a recent study in a sample of adults with type‐2 diabetes showed that interrupting sedentary time every 15 min with light‐intensity walking could be beneficial for glucose control 41 . This evidence has also been supported by recent compositional‐based 6,8 and other studies, 42,43 suggesting that increasing total physical activity volume through LPA can confer both mortality and cardiometabolic health benefits in adults, especially when LPA replaces sedentary behaviors 8,44 .…”
Section: Discussionsupporting
confidence: 90%
“…Experimental studies have generally supported this evidence and shown that avoiding prolonged sedentary bouts with light‐intensity activities (eg, walking) could be beneficial for cardiometabolic health in adults 3 . For instance, consistent with our results, a recent study in a sample of adults with type‐2 diabetes showed that interrupting sedentary time every 15 min with light‐intensity walking could be beneficial for glucose control 41 . This evidence has also been supported by recent compositional‐based 6,8 and other studies, 42,43 suggesting that increasing total physical activity volume through LPA can confer both mortality and cardiometabolic health benefits in adults, especially when LPA replaces sedentary behaviors 8,44 .…”
Section: Discussionsupporting
confidence: 90%
“…• Comparison. Studies that did not include a non-exercise control condition were excluded (23)(24)(25)(26)(27)(28)(29). Of these trials, the one by Bacchi et al (25) had been included in the qualitative synthesis of our 2013 systematic review.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The results of a recent study by suggest the frequency of brief activity breaks also impacts the magnitude of glycemic benefits [44,45] In summary, brief bouts of accumulated activity may be an attractive option for people with prediabetes and T2D who are highly sedentary and currently do not, and/or cannot, meet the recommended physical activity guidelines. However, few studies have compared brief activity breaks accumulated throughout the day to longer bouts of activity for improving glycemic control in T2D.…”
Section: Evidence From Acute Trials Of Accumulated Brief Activity Ver...mentioning
confidence: 99%